Development of factors contributing to barriers to paragraph writing for EFL learners - Sukserm, Patsawut; Masantiah, Chuthaphon; Tippayakulpairoj, Darunee (Institute of Advanced Engineering and Science, 2025)
Paragraph writing is an important aspect in the performance of English as a foreign language (EFL) learner, but most of them face significant barriers that hinder their writing performance. Though the importance of this skill is beyond doubt, there is an inadequate understanding of the factors leading to such challenges. Therefore, this study aimed to explore the barriers to paragraph writing for EFL learners. The validated 27-item questionnaire was administered to 619 EFL Thai students. An exploratory factor analysis (EFA) approach was employed to identify latent factors contributing to the barriers to paragraph writing. The results showed six key barriers to paragraph writing, explaining 60.224% of the total variance: structure and clarity challenges (SAC), focus and organizational barriers (FOB), writing process issues (WPI), timing and assessment worries (TAW), logical ideas challenges (LIC), and motivation and expression difficulties (MED). The findings suggest that there is a need to for greater emphasis on the learning environment, through proper planning and appropriate development of writing skills, to address the issues. Such factors are crucial for the improvement and success of EFL learners’ expectations in writing, which can go a long way towards building their confidence in paragraph writing.